Pengaruh Kualitas Pelayanan dan Experiential Marketing Terhadap Niat Pembelian Ulang Melalui Kepuasan Pelanggan Sebagai Variabel Intervening (Studi pada PT. JNE Kota Serang) - Ayatullah, Ayi; Meutia, Meutia; Lutfi, Lutfi (Jurnal Riset Bisnis dan Manajemen Tirtayasa, 2023)
E commerce transactions in Indonesia in 2022 reached 476 trillion and in 2018 only 105 trillion, indicating that the e commerce market share continues to increase. Competition between expedition service companies aims to retain consumers. this study examines the effect of service quality and experiential marketing on repurchase intentions through satisfaction as an intervening variable. this research was conducted at PT Jalur Nugraha Ekakurir (JNE) serang city. using quantitative methods using primary data obtained by filling out questionnaires. The population in this study amounted to 2,800 people is an average of every month consumers who send packages. With the number of samples in this study as many as 170 samples. The analytical tool used in this research is the SmartPLS Version 4.0.9.2 program. These results indicate that satisfaction is able to mediate the relationship between service quality and experiential marketing on repurchase intentions. With the position of the mediation variable partial mediation. This study reveals that service quality and experiential marketing have a positive and significant influence on repurchase intentions at PT Jalur Nugraha Ekakurir (JNE) Serang City.